Review Aktivitas Fotosintesis pada Tanaman Sorgum (Sorghum bicolor) dalam Kondisi Cekaman Kekeringan - Mukhamad Su'udi; Arsetyo Rahardianto; Miatin Alvin Septianasari; Veren Yuliana Saputri; Fuad Bahrul Ulum; Dwi Setyati (Rekayasa, 2022)
Sorghum (Sorghum bicolor L. Moench) is a cereal crop that has the potential to be developed in Indonesia as a food, feed and industrial crop. Sorghum is a C4 plant that has the advantage of efficiency in hot and dry environments. Drought stress is one of the most limiting environmental factors for crop productivity worldwide, and can be caused by water deficits in the soil and in the atmosphere. On the decreasing leaf water status, the rate of CO2 assimilation and the conductance of stomata decreased rapidly. The CO2 concentration mechanism is able to saturate C4 photosynthesis under the relatively low intercellular CO2 concentration. In addition, CO2 photorespiration is likely to be repaired before it exits the bundle sheat cells. The effects of non-stomatal factors include reduced activity of photosynthetic enzymes, inhibition of nitrate assimilation, induction of premature aging, and changes in leaf anatomy. Photosynthesis in C4 plants, including sorghum, involves, others, the PEPC and Rubisco enzymes. Drought can also trigger oxidative stress, which is an environmental condition that has increased Reactive Oxygen Species (ROS) due to an over reduction of the photosynthesis process.